Memperkuat tata kelola kedaulatan maritim Indonesia: Dimensi hukum dan kebijakan - ifthina, dzakiyatul - (Maliki Interdisciplinary Journal, 2026)
Indonesia, as the largest archipelagic country in the world, possesses significant maritime potential in economic, social, and geopolitical aspects. However, this potential is accompanied by various challenges in maintaining the sovereignty and security of its territorial waters. This article aims to analyze the strengthening of Indonesia’s maritime sovereignty governance from the perspective of law and policy. The method used is a literature study of relevant scientific sources. The results indicate that strengthening maritime sovereignty requires synergy between legal regulations, strict law enforcement, maritime diplomacy, and the empowerment of coastal communities. With strong governance, Indonesia can realize itself as a sovereign and sustainable global maritime axis.